2011
DOI: 10.4103/0019-5413.80042
|View full text |Cite
|
Sign up to set email alerts
|

Cementless bipolar hemiarthroplasty in femoral neck fractures in elderly

Abstract: Background:Cemented hip arthroplasty is an established treatment for femoral neck fracture in the mobile elderly. Cement pressurization raises intramedullary pressure and may lead to fat embolization, resulting in fatal bone cement implantation syndrome, particularly in patients with multiple comorbidities. The cementless stem technique may reduce this mortality risk but it is technically demanding and needs precise planning and execution. We report the perioperative mortality and morbidity of cementless bipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Relatedly, on study reported a patient experienced severe hypotension during the cementing procedure and died within 24 h of myocardial infarction ( 28 ). Therefore, some scholars believe that the elderly patients with significant cardiovascular risk factors should be given priority to the use of cementless bipolar hemiarthroplasty ( 52 ). A previous meta-analysis showed that the cemented hemiarthroplasty did not increase the risk of mortality, cardiovascular and cerebrovascular complications while achieving good postoperative results ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, on study reported a patient experienced severe hypotension during the cementing procedure and died within 24 h of myocardial infarction ( 28 ). Therefore, some scholars believe that the elderly patients with significant cardiovascular risk factors should be given priority to the use of cementless bipolar hemiarthroplasty ( 52 ). A previous meta-analysis showed that the cemented hemiarthroplasty did not increase the risk of mortality, cardiovascular and cerebrovascular complications while achieving good postoperative results ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…We read the article “Cementless bipolar hemiarthroplasty in femoral neck fractures in elderly” by Marya et al . 1 with interest. We congratulate the authors for their excellent work.…”
mentioning
confidence: 99%